33‐3: Student Paper: True Microdisplay with 3µm Pixel Size Using Deformed‐Helix Ferroelectric Liquid Crystal for VR/AR Displays. Issue 1 (28th June 2021) - Sun, Zhibo; Yuan, Zhengnan; Cheung, Alex; Shi, Runxiao; Kwok, Hoi-Sing; Srivastava, A. K.
Abstract : A glass‐based micro‐display with pixel size (<3µm) has been fabricated and verified in this work using deformed helix ferroelectric liquid crystal. High contrast (over 600:1), fast response time (< 400µs) and continuous gray scale within 5V driving voltage are achieved in the prototype.